Design and Development Classifications A Defect in Clay Tiles Using A Method of Support Factor Machine (SVM) - Rais Yufli Xavierullah; Murman Dwi Prasetio; Denny Sukma Eka Atmaja (School of Industrial and System Engineering, Telkom University, 2020)
Quality control is a system that can assist a company in maintaining and maintaining product quality sothat product defects do not occur. PT. XYZ is a company in the clay tile industry. Every month, PT. XYZhas products due to defects with an average of 2225 precarious. One of the problems that occurred at PT.XYZ is an inspection process that only uses sight. The use of sight can carry the risk of increased operatingcosts due to faulty examinations, failure to get business, and rework. With the development of technology,it can overcome this problem by finding artificial detectors using measurement methods, imagepreprocessing, and algorithms to detect defect. In this study using the Support Vector Machine (SVM)method in classifying defects. Taking pictures directly in this study using raspberry pi and making thealgorithm system using pyhton software. This study uses a linear kernel in the SVM algorithm. The resultsin this study concluded that the highest accuracy rate was 88.6% using a linear kernel.